Heart rate variability analysis in patients with multiple sclerosis - KEPEZ, ALPER; AĞAN YILDIRIM, KADRİYE; KAHRAMAN KOYTAK, PINAR (ELSEVIER SCI LTD, 2018)
Background: Multiple sclerosis can cause cardiovascular autonomic dysfunction. It is assumed that is caused by multiple demyelinating plaques localized in the brain stem and spinal cord. Previous studies have determined this using tilt table test, heart rate responses to Valsalva maneuver and deep breathing and heart rate variability analysis with 24 h Holier monitoring. However there is not a consensus regarding the presence of the relationship between autonomic dysfunction and severity of multiple sclerosis, type of multiple sclerosis and expanded disability status scale. The aim of the study is comparison of heart rate variability between recently diagnosed patients with relapsing-remitting multiple sclerosis and healthy controls by using 24 h Holier monitoring. Also we intended to investigate relationship between Expanded Disability Status Scale score, Multiple Sclerosis Functional Composite scores and cranial and spinal magnetic resonance imaging findings and hearth rate variability. Method: Fifty-one patients with newly diagnosed relapsing-remitting multiple sclerosis and 44 age- and sex-matched healthy controls were compared in this study. Patients with multiple sclerosis, who were already under immunomodulatory or immunosuppressive treatment, were excluded from the study. Echocardiography and hearth rate variability analysis using 24 h period Holier monitoring were performed in all of the subjects. Echocardiography was used to detect the presence of cardiac pathology. One multiple sclerosis patient with right ventricular dilatation and mobile intratrial septum was excluded from the study. All the patients underwent cranial and cervical spinal magnetic resonance imaging to determine the relationship between autonomic abnormalities and magnetic resonance imaging. Results: Our results showed that hearth rate variability values were significantly lower in patients with multiple sclerosis when compared with healthy controls: SDNN index (the mean of all the 5 min standard deviations of normal RR intervals during the 24 h period) (59.80 +/- 17.33 vs. 67.20 +/- 21.28, p = 0,044), the root-mean-square successive difference (rMSSD) (34.40 +/- 17.50 vs. 38.25 +/- 12.95, p = 0,042), spectral hearth rat variability total power (3738.84 +/- 2085.51 vs. 4427.44 +/- 1965.71, p = 0,037), spectral hearth rate variability low frequency (852.03 +/- 450.54 vs. 1011.75 +/- 370.06, p = 0,018). Ten patients (20%) had brainstem lesion, 25 patients (50%) had cervical lesions and 10 patients (20%) had thoracic spinal lesions on magnetic resonance imaging. There was no significant relationship between location of the lesions and heart rate variability analyses. Also there was no significant relationship between hearth rate variability values and Expanded Disability Status Scale score, Multiple Sclerosis Functional Composite scores or number of multiple sclerosis attack (p > 0,05). Conclusion: These findings reveals that our study population with multiple sclerosis had decreased heart rate variability compared to healthy controls. This was reflected by dysfunction of both parasympathetic and sympathetic parameters of hearth rate variability analysis. However, there is no significant relationship between hearth rate variability analysis and the findings on cranial, cervical, thoracic spinal magnetic resonance imaging findings, number of attack, Expanded Disability Status Scale score or Multiple Sclerosis Functional Composite scores in patients with multiple sclerosis.
Keywords: Multiple sclerosis; Heart rate variability; Autonomic dysfunction; CARDIOVASCULAR AUTONOMIC DYSFUNCTION; FUNCTIONAL COMPOSITE; NERVOUS-SYSTEM; MS